PENGARUH TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL) TERHADAP HARGA SAHAM (Studi Pada Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - Dila Anggraheni; Afifudin Afifudin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACT The purpose of this study is to determine and analyze the effect of variables NPL, GCG, ROA and CAR on the prices of public banking shares listed on the Indonesia Stock Exchange for the 2014-2017 period. The population in this study are all general banking companies listed on the Indonesia Stock Exchange. For samples taken in this study, 27 companies fulfilled the criteria for sample criteria. Sampling is done using the purposive sampling method. Secondary data is obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange for the period 2014-2017 with data collection methods using the documentation method. The analytical tool used is multiple linear regression analysis. By using the normality test method, classic assumption test (multicollinearity test, autocorrelation test, heteroscedastic test), hypothesis testing (F test, R2 test, t test).The results of the study show that NPL (Non Performing Loans), General Meeting of Shareholders (GMS), Board of Commissioners, Board of Directors, Audit Committee, NIM (Net Interest Margin) and CAR (Capital Adequacy Ratio) have simultaneous significant effect on the Share Price of the Company Banking listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. For NPL (Non Performing Loans) and NIM (Net Interest Margin) variables partially have a positive and significant effect on Banking Company Stock Prices listed on the Stock Exchange for the period 2014-2017. Good Corporate Governance that is proxied by (General Meeting of Shareholders (GMS), Board of Directors and Audit Committee) has a partial effect on Stock Prices in Banking Companies listed on the Stock Exchange for the period 2014-2017. While partially the Board of Commissioners does not have a significant influence on the share price of Banking Companies listed on the Stock Exchange for the period 2014-2017. CAR variable (Capital Adequacy Ratio) partially does not have a significant effect on the share price of Banking Companies listed on the Stock Exchange for the period 2014-2017. Keywords : General Banking, Stock Prices, NPL, GCG, ROA and CAR.